HELICOBACTER PYLORI: FROM DISCOVERY TO MODERN-DAY TREATMENTS - Band, Fatima Ahmed; Rashed, Mostafa Mohammed; ABD, mslim ALI; Hashim, Saif Salam; Hussein, Rawnaq Mahdi (PT. Antis International Publisher, 2024)
Helicobacter pylori, a Gram-negative bacterium, was first identified in the early 1980s as a major cause of chronic gastritis and peptic ulcer disease. Its discovery revolutionized the understanding of gastric pathology, shifting the paradigm from a solely acid-related etiology to one involving bacterial infection. This abstract provides a comprehensive overview of H. pylori, tracing its discovery, pathogenesis, and the evolution of treatment strategies. The initial identification of H. pylori by Barry Marshall and Robin Warren marked a pivotal moment in medical history, leading to widespread recognition of the bacterium's role in gastrointestinal diseases. The bacterium's unique ability to survive in the acidic environment of the stomach, coupled with its association with gastritis, peptic ulcers, and even gastric cancer, has driven extensive research into its biology and pathogenic mechanisms. Modern-day treatments for H. pylori have evolved significantly from the early use of single-agent antibiotics to the current standard of triple or quadruple therapy, which combines proton pump inhibitors (PPIs) with multiple antibiotics. This approach aims to overcome antibiotic resistance and enhance eradication rates. Newer treatment strategies also focus on optimizing therapy duration, minimizing side effects, and addressing resistance patterns. Advancements in diagnostic techniques, such as breath tests, stool antigen tests, and endoscopic biopsy-based methods, have improved the accuracy of H. pylori detection and monitoring. The ongoing research into alternative treatments, including novel antibiotics and probiotics, reflects a growing understanding of the bacterium's role in gastric diseases and the need for effective, personalized therapeutic approaches. In summary, the journey from the discovery of H. pylori to the development of modern treatments illustrates significant progress in gastrointestinal medicine. Continued research and innovation are essential to addressing the challenges of eradication and improving patient outcomes in the management of H. pylori-related diseases.